2016
DOI: 10.3329/bmj.v45i2.28980
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity with serum estrogen level in postmenopausal women

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Although we have previously demonstrated that 12 weeks of CRAE training and 12 weeks of resistance band-based training improves levels of estrogen in postmenopausal women [17,18], to our knowledge, it has not been documented how habitual CRAE training may impact estrogen levels in postmenopausal populations. Estrogen levels may be important to assess this in future studies of this type, since estrogen deficiency is thought to contribute to vascular dysfunction and hypertension in this population [9,12].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have previously demonstrated that 12 weeks of CRAE training and 12 weeks of resistance band-based training improves levels of estrogen in postmenopausal women [17,18], to our knowledge, it has not been documented how habitual CRAE training may impact estrogen levels in postmenopausal populations. Estrogen levels may be important to assess this in future studies of this type, since estrogen deficiency is thought to contribute to vascular dysfunction and hypertension in this population [9,12].…”
Section: Limitationsmentioning
confidence: 99%
“…Endothelial dysfunction and arterial stiffness are thought to precede CVD manifestation and have been reported to be independent predictors of cardiovascular event occurrence [10,11]. This vascular dysfunction and other risk factors, such as elevated BP, are thought to be partially attributed to estrogen deficiency, which may therefore put postmenopausal women at a higher risk for CVD manifestation [9,12]. These risk factors, if left alone, could contribute to a lower quality of life and ultimately increase the potential of CVD development and mortality in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of E 2 against hypertension during CIH exposure was apparently related to an attenuation of peripheral chemoreceptor activity, suggesting that E 2 likely reduces the activation of the sympathetic system during CIH exposure. On the other hand, it is well known that E 2 regulates the vascular tone, reduces the synthesis and release of endothelin‐1 (ET‐1) from endothelial cells and increases nitric oxide (NO) and antioxidant enzymes synthesis, thereby contributing to key differences in cardiovascular health between pre‐ and postmenopausal women …”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is an important mechanism of cardiovascular disease, especially atherosclerosis, and is associated with differences in sex [ 51 ]. Yeasmin et al suggested that lower estrogen levels could cause hypertension in postmenopausal women [ 52 ]; moreover, regular coffee consumption may be harmful to hypertension-prone individuals [ 53 ]. Approximately half (51.68%) of the female participants in our study were postmenopausal.…”
Section: Discussionmentioning
confidence: 99%